2006
DOI: 10.1086/503778
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Neutralizing Antibodies in Mother‐to‐Child Transmission of HIV‐1

Abstract: We analyzed the association between mother-to-child transmission (MTCT) of human immunodeficiency virus type 1 (HIV-1) and maternal neutralizing antibodies to heterologous primary isolates of various HIV-1 clades, to test the hypothesis that protective antibodies are those with broad neutralizing activity. Our study sample included 90 Thai women for whom the timing of HIV-1 transmission (in utero or intrapartum) was known. The statistical analysis included a conditional logistic-regression model to control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 41 publications
(51 reference statements)
6
39
0
Order By: Relevance
“…Several early studies, each relatively small, showed that nontransmitting mothers had more frequently detected and/or higher levels of NAb responses than transmitting mothers, suggesting a role for NAb in reducing MTCT (7,16,22,45,46). A correlation between maternal antibodies and transmission risk was also observed in a larger study of Thai women (n ϭ 90), in which the potency of NAb responses to 2 of 4 viruses tested inversely correlated with transmission (2,43). Subsequent studies showed that the variants transmitted to infants tended to be those in the mother that were the most resistant to NAbs (10,51).…”
mentioning
confidence: 77%
“…Several early studies, each relatively small, showed that nontransmitting mothers had more frequently detected and/or higher levels of NAb responses than transmitting mothers, suggesting a role for NAb in reducing MTCT (7,16,22,45,46). A correlation between maternal antibodies and transmission risk was also observed in a larger study of Thai women (n ϭ 90), in which the potency of NAb responses to 2 of 4 viruses tested inversely correlated with transmission (2,43). Subsequent studies showed that the variants transmitted to infants tended to be those in the mother that were the most resistant to NAbs (10,51).…”
mentioning
confidence: 77%
“…One study suggested HIV-1C viruses newly transmitted from mother-to-child were more fit, had significantly fewer PNG sites, and were more resistant to autologous maternal serum than nontransmitted viruses (60). For studies that analyzed vertical transmission stratified by timing, viral populations have been reported to have different properties if transmitted in utero (IU) or intrapartum (IP) (3,11,30).…”
Section: Subtype C Human Immunodeficiency Virus Type 1 (Hiv-1c) Contimentioning
confidence: 99%
“…Animal studies have demonstrated that neutralizing antibodies elicited by a simian immunodeficiency virus (SIV) vaccine can at least slow disease progression (56), while direct administration of antibodies matched to the chal-lenge virus can block transmission (16,44). Studies of natural MCTC have yielded conflicting results (2,3,7,20,26,31,32,48), although possibly for identifiable reasons. The breadth of the neutralizing antibody response may depend on the subtype of HIV-1 being studied (5,10), and neutralizing antibody levels may be associated with the timing of transmission (3).…”
Section: Subtype C Human Immunodeficiency Virus Type 1 (Hiv-1c) Contimentioning
confidence: 99%
See 1 more Smart Citation
“…The sub-Saharan region hosts the core of the pediatric HIV epidemic (46) mostly due to the transmission of subtype C strains, accounting for roughly 50% of all infections worldwide (19). Remarkably, it has been estimated that 60 to 80% of untreated infected mothers do not transmit the infection, suggesting that some yet-to-be-defined viral and/or host factors, including the generation and the transmission of neutralizing and/or blocking antibodies, can play a role in preventing MTCT transmission (6,47,48). This study focused on maternal gp41-specific antibodies, with particular reference to the mother-to-child transmission of their neutralizing potential via passive immunity.…”
mentioning
confidence: 99%